Wedding cakes, equality, and rhetorics of religious freedom. Issue 1 (3rd July 2019) - West, Isaac
ABSTRACT: Wedding cakes are a site of vigorous debate about the meaning and scope of religious freedom. Unfortunately, when we privilege religious freedom as a frame for understanding these controversies we do so at the expense of a fuller commitment to equality. In an analysis of three conservative news sources as well as three sites of discourse, small business, religious freedom, and wedding cakes, this essay explores how and why particular assertions of religious freedom inform the sense that religious freedom should be favored over the full and fair application of state and federal equality laws.